Solubility of Urea in ethanol-water mixtures and pure ethanol from 278.1K to 333.1K (2016)
This paper deals with the solubility of urea in ethanol-water mixtures in mole fractions of ethanol between 0.0901 and 1.000 at temperatures ranging from 278.1 to 333.1K. The investigation of solubility contributes to research in many others fields of study in chemical engineering, since there are several studies where the solubility of urea and its behavior in solution influence the system. The experiment was carried out at constant temperature, stirring for 2 hours and then leaving the solution at rest for 2 hours. After collecting the data, the solubility of urea was calculated based on the gravimetric method. The experimental results obtained were correlated with the temperature of the solvents using three equations based on the literature. The three models demonstrated results in line with the experimental data. It was observed that adding ethanol to the water decreased urea solubility in all cases. The differences between the predicted and the experimental values were on average 4.7%.